DEVELOPING ADULT LITERACY IN INDONESIA: A POLICY ANALYSIS OF GERAKAN INDONESIA MEMBACA (GIM) - Somantri, Cecep (2017)
This is a study in policy analysis. The purpose of the study is to explore Gerakan Indonesia Membaca (GIM) policy by using the framework of Bell and Stevenson (2013) which focuses on four dimensions of policy development and enactment. The data collected in this study originate from three sources, namely face-to-face interviews, policy documents and online archival materials. Based on the analysis, it is found that GIM is a product developed in response to literacy issues in which its development is largely influenced by the results of international surveys conducted by several powerful agents. The policy also has no clear meaning and objectives as it fails to precisely define ‘literacy’, and its basic concept is strongly associated with the ‘Uberfication’ of education policy. Nonetheless, educational leaders articulate this national policy by developing some activities in the corridor of their own role and function in the education system. At its final phase of enactment, GIM is manifested in the activities of teacher and tutor. For the Teacher, GIM has changed both ‘what she does’ and ‘who she is’. Meanwhile, for the Tutor, GIM has made no significant changes, since the policy is perceived to encapsulate what he does in daily practice.